Use of high performance computing in meteorology : (World Scientific, 2005)
Geosciences and, in particular, numerical weather prediction are demanding the highest levels of available computer power. The European Centre for Medium-Range Weather Forecasts, with its experience in using supercomputers in this field, organizes every other year a workshop bringing together manufacturers, computer scientists, researchers and operational users to share their experiences and to learn about the latest developments. This volume provides an excellent overview of the latest achievements and plans for the use of new parallel techniques in the fields of meteorology, climatology and oceanography.